Electronic Interactions of Michler's Ketone with DNA Bases in Synthetic Hairpins1. (31st October 2014) - Jalilov, Almaz S.; Young, Ryan M.; Eaton, Samuel W.; Wasielewski, Michael R.; Lewis, Frederick D.
Abstract The mechanism and dynamics of photoinduced electron transfer in two families of DNA hairpins possessing Michler's ketone linkers have been investigated by means of steady state and time‐resolved transient absorption and emission spectroscopies. The excited state behavior of the diol linker employed in hairpin synthesis is similar to that of Michler's ketone in methanol solution. Hairpins possessing only a Michler's ketone linker undergo fast singlet state charge separation and charge recombination with an adjacent purine base, attributed to well‐stacked ground state conformations, and intersystem crossing to the triplet state, attributed to poorly stacked ground state conformations. The failure of the triplet to undergo electron transfer reactions on the 7 ns time scale of our measurements is attributed to the low triplet energy and reduction potential of the twisted triplet state. Hairpins possessing both a Michler's ketone linker and a perylenediimide base surrogate separated by four base pairs undergo photoinduced hole transport from the diimide to Michler's ketone upon excitation of the diimide. The efficiency of hole transport is dependent upon the sequence of the intervening purine bases.